1990
DOI: 10.1007/bf01644187
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus in patients with cystic fibrosis: An epidemiological analysis using a combination of traditional and molecular methods

Abstract: An epidemiological analysis of Staphylococcus aureus was conducted in a study group of 157 cystic fibrosis patients cultured over a 30-month period. The resulting S. aureus isolates were categorized by bacteriophage type, plasmid profile, and (in some instances) chromosomal restriction fragment pattern of the culture-positive patients with S. aureus (34 of 157) 44% only were sporadically infected while 68% shared identical strains with one or more other patients. Six patients exhibited persistent infection (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This propensity to cause chronic infections is thought to be related, at least in part, to the persistence of SCVs within nonphagocytic host cells (39). Antibiotic treatments often are ineffective against S. aureus infecting CF lungs, and relapsing infections are often observed (13,18). These relapsing infections are thought to be caused by bacteria persisting inside host cells in the lungs (21).…”
Section: Discussionmentioning
confidence: 99%
“…This propensity to cause chronic infections is thought to be related, at least in part, to the persistence of SCVs within nonphagocytic host cells (39). Antibiotic treatments often are ineffective against S. aureus infecting CF lungs, and relapsing infections are often observed (13,18). These relapsing infections are thought to be caused by bacteria persisting inside host cells in the lungs (21).…”
Section: Discussionmentioning
confidence: 99%
“…These DNA-based molecular methodologies, which will be examined extensively in this review, include pulsed-field gel electrophoresis (PFGE) and other restriction-based methods, plasmid analysis, and PCR-based typing methods. The incorporation of molecular methods for typing of nosocomial patho-gens has assisted in efforts to obtain a more fundamental assessment of strain interrelationship (1,7,8,55,82,103,(105)(106)(107)(108)(109)(110)(111)138). Establishing clonality of pathogens can aid in the identification of the source (environmental or personnel) of organisms, distinguish infectious from noninfectious strains, and distinguish relapse from reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Staphylococcus aureus is an initial and chronic colonizer of the mucus gel present in the airways of patients with cystic fibrosis (CF) (Burns & May, 1968;Goerging et al, 1990;Marks, 1990). Bauernfeind et al (1987) reported a longitudinal study of sputa from 102 patients with CF in which the incidence of S. aureus and S. epidermidis was approximately 36 %.…”
Section: Introductionmentioning
confidence: 99%